2012 International Conference on Field-Programmable Technology 2012
DOI: 10.1109/fpt.2012.6412110
|View full text |Cite
|
Sign up to set email alerts
|

FPGA optimized packet-switched NoC using split and merge primitives

Abstract: Abstract-Due to their different cost structures, the architecture of switches for an FPGA packet-switched Networkon-a-Chip (NoC) should differ from their ASIC counterparts. The CONNECT network recently demonstrated several ways in which packet-switched FPGA NoCs should differ from ASIC NoCs. However, they also concluded that pipelining was not appropriate for the FPGA switches. We show that the Split-Merge switch architecture is more amenable to pipelining on FPGAs, achieving 300MHz operation-up to three times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Some have suggested that VCs consume area and power excessively [Huan and DeHon 2012]. We investigate a one-VC version of our hard NoC with hard links and find that it does, in fact, improve area per BW.…”
Section: Hard and Soft Nocsmentioning
confidence: 95%
“…Some have suggested that VCs consume area and power excessively [Huan and DeHon 2012]. We investigate a one-VC version of our hard NoC with hard links and find that it does, in fact, improve area per BW.…”
Section: Hard and Soft Nocsmentioning
confidence: 95%
“…Often a time-multiplexed overlay network can be more efficient than a packet-switched network [75]. Because of the different cost structure between ASICs and FPGAs, overlay NoCs on FPGAs should be designed differently from ASIC NoCs [76], [77]. Ultimately, it may make sense to integrate packet-switched NoC support directly into the FPGA fabric [78].…”
Section: )mentioning
confidence: 99%
“…Next, we look at the overhead of VCs by investigating a one-VC version of our hard NoC running at 0.9 V. Some have suggested that VCs consume area and power excessively [5]. Table 3 confirms that supporting multiple VCs does reduce energy efficiency.…”
Section: Comparing Nocs and Fpga Interconnectmentioning
confidence: 99%
“…Both soft NoCs [3][4][5] and hard NoCs [6,7] have been introduced in the context of FPGAs, but power consumption was seldom analyzed. However, there is an extensive body of work discussing the power consumption of NoCs for multiprocessors.…”
Section: Introductionmentioning
confidence: 99%